Blended Project-Based Learning Model on 21st Century Skills: A Qualitative Content Analysis - Kharisma Diastuti; Rahma Diani; Antomi Saregar; Adyt Anugrah; Megawati Ridwan Fitri (Engiscience Publisher, 2024)
The 21st century has revolutionized education with technology, but challenges such as teachers' resistance, students' comprehension issues, effective implementation, and teacher training persist. This study employs a qualitative content analysis to document and analyze data from 18 research studies on blended project-based learning models. It aims to identify the stages, research methods, subject areas, and educational levels that most frequently implement this model. Data was col-lected from Google Scholar, Scopus, and ERIC databases over the past five years (2019-2023). Findings reveal that 7 out of 18 journals discuss blended project-based learning models with sim-ilar syntax. Key findings include: (i) the combination of face-to-face and online learning enhances effectiveness; (ii) quasi-experimental methods are prevalent, particularly in biology and higher education; and (iii) blended project-based learning effectively improves 21st century skills, in-cluding critical thinking (mean effect size 1.65), creativity (mean effect size 1.19), and prob-lem-solving (mean effect size 1.44), resulting in an overall mean effect size of 1.42.